Proceso de aprendizaje de un estudiante con discapacidad intelectual en la UPS - Tapia Gordón, Andrea Beatriz (2018)
The purpose of the present case analysis is to demonstrate the learning process of a person with intellectual disability in higher education. The study was conducted based on the needs of the student, for which it was important to know the learning style of the student who is studying the Management and Leadership Career at the Polytechnic University Salesiana (UPS). The research was organized based on the identification of a problem: the ignorance of students with disabilities in the university environment, therefore, there is no action plan to accompany these students in their learning process, followed by the construction of a conceptual framework with the topics that guide the research: learning, intellectual disability and inclusive education. Second, it establishes the methodology, which allows gathering information from the qualitative and interpretative method, supported by the ethnographic study, for its respective analysis and presentation of findings. The relevance of this work is to determine the learning process of a student with disabilities, which can serve as a reference for other students with or without disabilities and offer adequate support to enhance their personal growth. The present work is carried out according to the approaches of Vygotsky and Piaget who base that all the people possess a style of learning, the same one that depends on the social context. This work is of vital importance for future research and for the teaching exercise, since it provides theoretical reference to build personalized supports in higher education.